Rumi and Adding "-i" Suffixes to Words Ending in the [i] Vowel - Hamidreza Tvakkoli (مطالعات زبانی و بلاغی)
Adding "-i" suffixes to words ending in the [i] vowel creates an odd pronunciation. Although there has been a tendency to avoid this phonetic occurrence, Dari Persian has shown evidences of this phenomenon for a long time. In Rumi's poetry, these pieces of evidence are abundant and appear more as forms of defamiliarization that show distinction and emphasis. In this way, he places a phonetic anomaly in the realm of his aesthetic norms. On the other hand, this stylistic distinctive creates a sign indicating the uniqueness of his experiences and the moments he talks about. In this way, it paves the way from formal and phonetic phenomena to narrow mystical significations. It should be noted that this article is a report on a much broader research that has been prepared over the years based on the numerous shreds of evidence in Rumi’s works and Persian poetry and prose that will be published in the future.